Strategi Manajemen Pengelolaan Perpustakaan dalam Menunjang Proses Pembelajaran Siswa di SMK Samudera Buana Langkaplancar - Nanu Andriani; Doni Ilyas; Manarul Hidayat (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2024)
This research aims to implement library management strategies. School libraries play an important role in supporting teaching and learning activities, but they are often not managed optimally. School libraries are frequently not well-managed despite being crucial for supporting the teaching and learning process. This aligns with library management strategies, including diverse collections relevant to the curriculum, collaboration between teachers and librarians, easy accessibility, and efficient classification and cataloging. The method used is qualitative, involving interviews, observations, and review of previous journals (library research). The results of the research conducted show that library management strategies can be implemented in library management to support student learning in educational institutions through: 1. Collection, 2. Collaboration, 3. Accessibility, 4. Management